2021
DOI: 10.1183/23120541.00658-2020
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of serum extracellular vesicles identifies a novel COPD biomarker, fibulin-3 from elastic fibres

Abstract: There is an unmet need for novel biomarkers in the diagnosis of multifactorial COPD. We applied next-generation proteomics to serum extracellular vesicles (EVs) to discover novel COPD biomarkers.EVs from 10 patients with COPD and six healthy controls were analysed by tandem mass tag-based non-targeted proteomics, and those from elastase-treated mouse models of emphysema were also analysed by non-targeted proteomics. For validation, EVs from 23 patients with COPD and 20 healthy controls were validated by target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…COPD) can alter the composition and packaging of proteins, mRNA and ncRNAs in EVs/exosomes Ex vivo Human In vitro RNA-seq analysis carried out on EVs from plasma samples of human subjects showed significant miRNAs up- or down-regulated in smokers vs. COPD and non-smokers vs. COPD pairwise comparisons Jung et al, 2020 [ 54 ] Surface proteome of plasma extracellular vesicles as biomarkers for pneumonia and acute exacerbation of chronic obstructive pulmonary disease Identify surface proteins of plasma small EVs (ssEVs) as biomarkers for diagnosis and differentiation of AECOPD to CAP (community acquired pneumonia) Ex vivo Human There was a significantly higher expression in plasma sEVs (CD45, CD28, CTLA4, TNF-R-II, and CD16) from patients with AECOPD when compared to CAP patients, allowing for discrimination between the two Koba et al . , 2021 [ 55 ] Proteomics of serum extracellular vesicles identifies a novel COPD biomarker, fibulin-3 from elastic fibres Assess serum EVs to find novel biomarkers for personalised medicine in COPD using the latest proteomic strategies Ex vivo Human In vivo Mice This study identified novel biomarkers for COPD using next-generation proteomics of serum extracellular vesicles. Notably, the expression of fibulin-3 is correlated with lung function and emphysema Soni et al, 2021 [ 56 ] Intra-alveolar neutrophil-derived microvesicles are associated with disease severity in COPD Evaluate the profiles of intra-alveolar (within BALF) and circulating (within plasma) MVs in COPD patients, characterizing a variety of MV subtype populations Ex vivo Human This study identified a variety of MV subtype populations within the BALF and plasma of COPD patients with a spectrum of disease severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD) can alter the composition and packaging of proteins, mRNA and ncRNAs in EVs/exosomes Ex vivo Human In vitro RNA-seq analysis carried out on EVs from plasma samples of human subjects showed significant miRNAs up- or down-regulated in smokers vs. COPD and non-smokers vs. COPD pairwise comparisons Jung et al, 2020 [ 54 ] Surface proteome of plasma extracellular vesicles as biomarkers for pneumonia and acute exacerbation of chronic obstructive pulmonary disease Identify surface proteins of plasma small EVs (ssEVs) as biomarkers for diagnosis and differentiation of AECOPD to CAP (community acquired pneumonia) Ex vivo Human There was a significantly higher expression in plasma sEVs (CD45, CD28, CTLA4, TNF-R-II, and CD16) from patients with AECOPD when compared to CAP patients, allowing for discrimination between the two Koba et al . , 2021 [ 55 ] Proteomics of serum extracellular vesicles identifies a novel COPD biomarker, fibulin-3 from elastic fibres Assess serum EVs to find novel biomarkers for personalised medicine in COPD using the latest proteomic strategies Ex vivo Human In vivo Mice This study identified novel biomarkers for COPD using next-generation proteomics of serum extracellular vesicles. Notably, the expression of fibulin-3 is correlated with lung function and emphysema Soni et al, 2021 [ 56 ] Intra-alveolar neutrophil-derived microvesicles are associated with disease severity in COPD Evaluate the profiles of intra-alveolar (within BALF) and circulating (within plasma) MVs in COPD patients, characterizing a variety of MV subtype populations Ex vivo Human This study identified a variety of MV subtype populations within the BALF and plasma of COPD patients with a spectrum of disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al [ 60 ] observed that expression levels of three exosomal miRNAs were negatively associated with FEV1. Koba et al [ 55 ] study observed that expression of fibulin-3 correlated with lung function and emphysema. Together these studies indicate that EVs can lead to the development of more accurate biomarkers to diagnose COPD and monitor disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…3A ; Table 2 ; Supplementary Table 2 ). Targeted proteomics enables the efficient and specific verification of candidates without requiring antibodies and is, thus, a powerful tool for biomarker validation ( 14 , 15 , 20 ). Among the 25 biomarker candidates, the expression levels of LBP and the monocyte differentiation antigen CD14 were markedly elevated in patients with sarcoidosis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some comparative studies have shown that the isolation of EVs by SEC retains the biophysical properties of EVs, and results in a higher yield ( 13 ). Tandem mass tag-based non-targeted proteomic analysis of serum EVs isolated by ultracentrifugation revealed that fibulin-3 in EVs may serve as a novel diagnostic biomarker for chronic obstructive pulmonary disease (COPD) and might be closely related to its pathophysiology ( 14 ). With this background, we isolated serum EVs using SEC, which can detect less abundant serum proteins, and applied label-free proteomic strategies to discover novel biomarkers for sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Although multiple sample resources are available, peripheral blood has been regarded as an ideal source due to its reproducibility of measurement and feasibility of access. 15 However, 99% of serum proteins, including albumin, immunoglobulins, and complement factors, will mask some biomarker candidates when measured by conventional proteomics. To break down these barriers, we focused on proteomic profiling of EVs.…”
Section: Introductionmentioning
confidence: 99%